Three-dimensional shape measurement based on binary fringe conventional projection. (October 2019) - Fu, Guangkai; Cao, Yiping; Wang, Yapin; Wan, Yingying; Wang, Lu; Li, Chengmeng
A three-dimensional (3D) shape measurement method based on binary fringe conventional projection is proposed. In traditional 3D shape measurement methods based on binary fringe projection, the binary fringe is used as an approximate sinusoidal fringe by defocusing projection or even directly used as an approximate sinusoidal fringe by nonlinear error suppression feature of large-step phase measuring profilometry (PMP). In the proposed method (Prop), neither defocusing projection is needed nor large-step PMP must be used. When the binary fringe is conventionally projected on the measured object, just by filtering operation in spatial frequency domain from the captured deformed pattern, the nearly unbroken sinusoidal deformed pattern can be extracted efficiently. While N ( N ≥3) frames binary fringes with 1/ N period misalignment between each adjacent fringe are conventionally projected onto the measured object sequentially, the corresponding nearly unbroken N -step sinusoidal deformed patterns extracted from the N frames captured deformed patterns can be used to reconstruct the 3D shape of the measured object with N -step PMP algorithm. The experimental results show the feasibility and validity of the Prop. It is more flexible for its optional fringe period and optional phase-shifting steps. It has potential application in the real-time 3D shape measurement.